2019
DOI: 10.1101/559922
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Genomic Ecosystem of Transposable Elements in Maize

Abstract: Transposable elements (TEs) constitute the majority of flowering plant DNA, reflecting their tremendous success in subverting, avoiding, and surviving the defenses of their host genomes to ensure their selfish replication. More than 85% of the sequence of the maize genome can be ascribed to past transposition, providing a major contribution to the structure of the genome. Evidence from individual loci has informed our understanding of how transposition has shaped the genome, and a number of individual TE inser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 126 publications
5
73
0
Order By: Relevance
“…If gene fragments provide camouflage for TEs, one reasonable prediction is that they will exist within the genome for longer periods of time than free TEs. Using the inferred age of elements from a previous study 34 , we found that this is indeed the case (Figure 4a). The above differences were principally caused by Sirevirus elements, perhaps in part reflecting their higher proportion of free TEs.…”
Section: The Case For Conflict: Tessupporting
confidence: 54%
See 3 more Smart Citations
“…If gene fragments provide camouflage for TEs, one reasonable prediction is that they will exist within the genome for longer periods of time than free TEs. Using the inferred age of elements from a previous study 34 , we found that this is indeed the case (Figure 4a). The above differences were principally caused by Sirevirus elements, perhaps in part reflecting their higher proportion of free TEs.…”
Section: The Case For Conflict: Tessupporting
confidence: 54%
“…To test the first idea, we used age estimates from terminal branch lengths of TE phylogenetic trees generated by Stitzer at al. (2019) 34 . We found that TEs with captured fragments are older than free TEs (mean of 0.134 vs. 0.066 million years, one-sided Mann-Whitney-Wilcoxon Test p<2.2e-16; Figure 4a), suggesting that they have remained intact within the genome for longer periods.…”
Section: Potential Advantages For Tes To Capture Gene Fragmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…But at the same time, the range in repeat content among eukaryotic genomes is great, with some species having a scant number of repetitive elements (0.8% in one species of bdelloid rotifer (Nowell, et al * Correspondence: gavincw@uoregon.edu 2018)). And not only does the global repeat content among genomes vary-heterogeneity in repeat content both within and between chromosomes occurs (Rizzon, et al 2002;Stitzer, et al 2019). Furthermore, repeat density in genomes has been observed to covary with patterns of genomic diversity (Clark, et al 2007), recombination rate (Rizzon, et al 2002), gene density (Medstrand, et al 2002), chromatin state (Peng and Karpen 2008), centromeric regions (Plohl, et al 2014) and physical spatial position (Guelen, et al 2008).…”
Section: Introductionmentioning
confidence: 99%